2021
DOI: 10.1177/02537176211000769
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of the Caregivers in Managing a Child with Autism Spectrum Disorder— A Qualitative Analysis

Abstract: Background: Autism spectrum disorder (ASD) is a complex neurological condition resulting in impaired social interaction and difficulty in understanding verbal and nonverbal communication. Caring for children with ASDs is challenging for both children and their caregivers. The child suffering from ASD starts to show the developmental outcome during early 2.5–3 years and continues thereafter till the child turns to an adult. Many caregivers face severe financial crises, high out-of-pocket healthcare expenses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Therefore, although the main reasons identified as causes of anxiety and reduced perceived quality of life have not been investigated in the present study, several factors involved in caring for a child with autism may be related. Tathgur and Kang [27] aimed to assess the concerns of caregivers of children with ASD and observed that caregivers face several challenges that negatively impact their physical health, psychological well-being, social reactions, and financial balance. Additionally, caregivers reported concerns related to the availability of ASD services and poorly coping with the diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the main reasons identified as causes of anxiety and reduced perceived quality of life have not been investigated in the present study, several factors involved in caring for a child with autism may be related. Tathgur and Kang [27] aimed to assess the concerns of caregivers of children with ASD and observed that caregivers face several challenges that negatively impact their physical health, psychological well-being, social reactions, and financial balance. Additionally, caregivers reported concerns related to the availability of ASD services and poorly coping with the diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the main reasons identified as causes of anxiety and reduced perceived quality of life have not been investigated in the present study, several factors involved in caring for a child with autism may be related. Tathgur and Kang [25] aimed to explore the concerns of the caregivers of children suffering from ASD, and they observed that caregivers face various challenges while caring for a child with ASD, with a negative impact on physical health, psychological wellbeing, societal reactions, and financial balance. Caregivers reported concerns related to service availability for ASD, poorly coping with the diagnostics, and disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is an extremely daunting task to find the right person to look after a child with autism because there are so many concerns attached to it that you do not see when caring for a neurotypical child. Many caregivers may face many problems when the child is under their care, ranging from stress, restriction of other activities, anxiety, and diminished physical health (Tathgur et al, 2021).…”
Section: Theme 2: Difficulties and Struggles Of Parenting A Child Wit...mentioning
confidence: 99%